Book Review- Developing the Global Student: Higher Education in an Era of Globalization Internationalization in Higher Education Series - Nasser, Jr., Roger "Mitch" (Journal of International Students, 2017)
While administrators may consider increasing their international student population as a plausible solution to the enrollment crisis, they must also consider how these students navigate the campus environments. What are our responsibilities as higher education administrators? How will U.S. students respond to their international classmates? Moreover, will native students understand and accept the differences they encounter? David Killick’s book, Developing the Global Student: Higher Education in an Era of Globalization asks how prepared students are for the international community. Killick’s discussion methods include philosophy, student development, and self-reflection, which will appeal to most readers.